The Mediating Role of Emotional Intelligence in Enhancing the Effect of Leadership Competencies on Service Quality in Jordanian Private Hospitals: An Empirical Study from Managers’ Perspective - Alhalalmeh, Mohammad; Al-Nabulsi, Manwa; Awamleh, Hassan (Jordan Journal of Business Administration, 2018)
The aim of the current study is to examine the mediating role of emotional intelligence in enhancing the effect of leadership competencies on service quality in Jordanian private hospitals from managers’ perspective. The study adopts the analytical descriptive approach. The study population consisted of all Jordanian private hospitals. The study sample consisted of Jordanian private hospitals in Amman. The unit of analysis consisted of managers working in Jordanian private hospitals in Amman, totaling 73. The results revealed that there is a direct positive effect of leadership competencies on service quality in Jordanian private hospitals at the significance level α ≤0.05. The results also showed that there is a direct positive effect of leadership competencies on emotional intelligence in Jordanian private hospitals at the significance level α ≤0.05 and that there is a direct positive effect of emotional intelligence on service quality in Jordanian private hospitals at the significance level α ≤0.05. It was concluded that emotional intelligence plays a positive mediating role in enhancing the effect of leadership competencies on service quality in Jordanian private hospitals. The study recommends that more emphasis should be placed on leadership competencies and quality of services, espcially in Jordanian private hospitals which, in turn, reflects the decision quality in those hospitals.